The Effect of Fear of Missing Out, Celebrity Endorsements and Advertisements on Impulsive Buying, Case Study: Brand Skintific on The Tiktok Application - Shofaranti, Isna; Putri, Haniva Azzahra Hidayat; Maulana, Yono (Ridwan Institute, 2024)
This study aims to examine the effect of fear of missing out, celebrity endorsements and advertising on impulsive buying. This study involved 150 respondents domiciled in Ciayumajakuning, selected through a purposive sampling procedure. The analysis method used is a quantitative method. The population of this study is the ciayumajakuning community who have purchased skintific brands on the TikTok application. The results showed that Fear of missing out had a significant positive effect on impulsive buying. Then celebrity endorsements have a positive and significant effect on impulsive buying. In addition, advertising has also proven a relationship between fear of missing out and celebrity endorsements with impulsive buying. This research provides a deeper understanding of the factors that influence impulsive buying in skintific brands on official TikTok. Thus, this study makes an important contribution in understanding the relationship between fear of missing out, celebrity endorsement, advertising and impulsive buying in the context of skintific brands.